Pulmonary cryptococcosis in the setting of immunosuppression by methylprednisolone monotherapy for oral pemphigus: a case report and literature review - Mei, Hongxia; Bao, Pengchen; Wang, Yongxu; Wei, Zhijing; Yang, Qin; Chen, Chen; Sun, Yakai; Su, Xinming; Kang, Jian; Li, WenYang (Frontiers in Medicine, 2025)
Cryptococcosis is an opportunistic and potentially fatal fungal infectious disease. Pemphigus diseases are characterized by blistering of the cutaneous and mucous membranes. We report a case of pulmonary cryptococcosis (PC) following methylprednisolone treatment for pemphigus vulgaris. Additionally, we analyzed a case series of PC infections recorded in PUBMED from 2013 to 2023. A total of 229 cases of PC were included. The median age was 54 years, with 66.4% of patients being male. Those with previous use of corticosteroids or immunosuppressives accounted for 38.4% of cases. Underlying conditions included solid organ transplantations (25.7%), respiratory diseases (6.6%), malignant tumors (6.1%), rheumatoid arthritis (5.7%), hematological malignancies (4.4%), among others. The main source of infection was exposure to birds, poultry, and their feces (12.7%). Cryptococcus neoformans was most frequently isolated (76.4%). Overall mortality was 14.8%. Previous use of corticosteroids or immunosuppressants was a risk factor for disseminated cryptococcus (p < 0.05). Age, underlying disease, dissemination, and no antifungal therapy were independently associated with increased mortality (p < 0.05). Co-occurrence of pemphigus and PC is rare. Prompt diagnosis and appropriate treatment of PC are essential to prevent fatal consequences. Corticosteroids or immunosuppressive therapy are associated with the development of disseminated cryptococcal infection. Age, underlying disease, and dissemination are related to increased mortality. Timely antifungal therapy can improve prognosis.